Bicameralism for Pluralism in a Multiethnic Society and Its Perspectives in Georgia - Jibgashvili, Zurab; Marinashvili, Marine (European Scientific Journal, ESJ, 2026)
This article examines the constitutional role and institutional formation of bicameralism in multiethnic societies, with particular focus on the composition and constitutional competencef the upper chamber. It argues that bicameralism constitutes a fundamental mechanism for strengthening democratic legitimacy, balancing state power and ensuring the effective representation of diverse social groups. Contrary to claims that it fragments popular sovereignty, the study demonstrates that bicameralism reinforces it through internal checks and balances and enhanced inclusivity. Drawing on comparative analysis of European and Post-Socialist states, the article evaluates different models of upper chamber formation: direct, indirect, appointed, and mixed, and their implications for legitimacy, representation and institutional effectiveness. Particular attention is given to the relationship between the method of formation and the functional identity of the upper chamber, emphasizing the advantages of asymmetrical bicameralism and territorial representation in multiethnic contexts. The study highlights both the integrative potential and the risks of mechanisms such as ethnic quotas and veto powers. The research further analyzes the constitutional framework of Georgia, exploring the conditional provision for bicameralism and its linkage to the restoration of territorial jurisdiction. It argues for a more flexible, teleological interpretation more flexible, teleological interpretation of the constitutional text/norm, that would that would allow earlier institutional development. The findings suggest that a territorially representative and functionally distinct upper chamber could enhance political pluralism, reduce excessive centralization and strengthen democratic consolidation in Georgia.